Non–wood forest products used by temiar community in Kampong Lata Janggut, Jeli, Kelantan - Abd Latif, Muhamad Azim Syahmi (2019)
Non-Wood Forest Products (NWFPs) include foods (nuts, fruits, mushroom, honey), food additives (spices, herbs), fibers (furniture) plant and animal products with medicinal value. Deforestation means loss of forests or loss of vegetal cover in the forest. This forest issue contributes to increment of poverty and susceptible conditions of Temiar community in the region. This study was conducted in Kampong Lata Janggut, Jeli, Kelantan and the objectives were to determine the agroforestry by Temiar communities in Kg. Lata Janggut, Jeli and to examine the non-wood forest products produce from agroforestry activities by the communities. During this study, data were collected such as gender, age, education level, family numbers and occupation using questionnaire method. Among 90 of respondents were selected randomly and two data analysis were done. 68 % of the respondents are male and 28 % are female. Based on this study, there are five types of activities that carried out by Temiar community in Kampong Lata Janggut Jeli,Kelantan. The most recent activities that they conduct are forest product gathering, second is plantation sector, third is others activities, fourth is handicraft, and the last one is logging sector. The forest product that collected by Temiar community, it can be divided into three categories. The first category is flora, second is fauna, and last is other. Recommendations of the study were also highlighted.